PLATELET COUNT IN MALARIA PATIENTS - Shaikh, Mumtaz Ali; Ahmed, Shakeel; Diju, Inayat Ullah; Yakta, Dur -E- (Journal of Ayub Medical College Abbottabad, 2011)
Background: Malaria is a major health problem in the tropics with high morbidity and mortality. This study is conducted to analyse the effects of malaria on platelets. Methods: This prospective study was conducted on 200 diagnosed cases of malaria in Department of Medicine, LUMHS, Jamshoro/Hyderabad from February to December 2010. The diagnosis of malaria was carried out by thin and thick blood films. Platelet count was performed using an automated counter. Thrombocytopenia was classified as mild (50-150ï‚´103 cells/µl), moderate (20-50ï‚´103 cells/µl) and severe (<20ï‚´103 cell/µl). Results: The age of patients ranged from 16 to 80 (28±10.5) years, median age was 30 years. Among the study population, males were 124 (62%) and females were 76 (38%). Out of them 105 (52.5%) were cases of Plasmodium falciparum, 93 (46.5%) were of P. vivax, and 2 (1%) were of P. malaria. The data showed that 171 (85.5%) patients were having low platelet count; 141 (70.5%) had mild, 21 (10.5%) moderate, and 9 (4.5%) had severe thrombocytopenia. Twenty-nine (14.5%) patients had normal platelet count. Conclusion: Malaria is associated with different degrees of low platelet count with rarely increased bleeding tendency. Keywords: Malaria, Falciparum, Platelets